2020
DOI: 10.33160/yam.2020.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Is X-linked Recessive Ichthyosis a High Risk for Basal Cell Carcinoma?

Abstract: We report a case of X-linked recessive ichthyosis with basal cell carcinoma. An 86-year-old man was referred to our department for evaluation of a 1-year history of an ulcer on his left leg. He had suffered from dry skin with scales on his entire body since childhood. Histopathological examination of the lower leg revealed intradermal proliferation of a solid nest of basaloid cells showing unclear palisading in the periphery. Marked hyperkeratosis and hypergranulosis were also seen in the adjacent dermis. Loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Similarly, filaggrin mutations are associated with greater risks for developing atopic dermatitis, a condition that is associated with higher risks for nonmelanoma skin cancer. Finally, some have speculated that the chronic inflammation associated with the impaired skin barrier in ichthyosis could contribute to carcinogenesis (Wakumoto et al, 2020). Despite these findings, the true relationship between ichthyosis and skin cancer risk remains unclear (Natsuga et al, 2011; Skaaby et al, 2014); however, given the potential association, some have suggested that patients with IV undergo lifelong skin cancer surveillance (Tas et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, filaggrin mutations are associated with greater risks for developing atopic dermatitis, a condition that is associated with higher risks for nonmelanoma skin cancer. Finally, some have speculated that the chronic inflammation associated with the impaired skin barrier in ichthyosis could contribute to carcinogenesis (Wakumoto et al, 2020). Despite these findings, the true relationship between ichthyosis and skin cancer risk remains unclear (Natsuga et al, 2011; Skaaby et al, 2014); however, given the potential association, some have suggested that patients with IV undergo lifelong skin cancer surveillance (Tas et al, 2017).…”
Section: Discussionmentioning
confidence: 99%